Altered Brain Structure and Functional Connectivity and Its Relation to Pain Perception in Girls With Irritable Bowel Syndrome. Issue 2 (February 2019) - Bhatt, Ravi R.; Gupta, Arpana; Labus, Jennifer S.; Zeltzer, Lonnie K.; Tsao, Jennie C.; Shulman, Robert J.; Tillisch, Kirsten
ABSTRACT: Objective: Imaging studies in adults with irritable bowel syndrome (IBS) have shown both morphological and resting state (RS) functional connectivity (FC) alterations related to cortical modulation of sensory processing. Because analogous differences have not been adequately investigated in children, this study compared gray matter volume (GMV) and RS-FC between girls with IBS and healthy controls (HC) and tested the correlation between brain metrics and laboratory-based pain thresholds (Pth). Methods: Girls with Rome III criteria IBS ( n = 32) and matched HCs ( n = 26) were recruited. In a subset of patients, Pth were determined using a thermode to the forearm. Structural and RS scans were acquired. A voxel-based general linear model, adjusting for age, was applied to compare differences between groups. Seeds were selected from regions with group GMV differences for a seed-to-voxel whole brain RS-FC analysis. Significance for analyses was considered at p < .05 after controlling for false discovery rate. Significant group differences were correlated with Pth. Results: Girls with IBS had lower GMV in the thalamus, caudate nucleus, nucleus accumbens, anterior midcingulate (aMCC), and dorsolateral prefrontal cortex. They also exhibited lower RS-FC between the aMCC and the precuneus, but greater connectivity between the caudate nucleus and precentral gyrus. Girls with IBS had higher Pth with a moderate effect size ( t (22.81) = 1.63, p = .12, d = 0.64) and lower thalamic GMV bilaterally was correlated with higher Pth (left: r = −.62, p (FDR) = .008; right: r = −.51, p (FDR) = .08). Conclusions: Girls with IBS had lower GMV in the PFC, basal ganglia, and aMCC, as well as altered FC between multiple brain networks, suggesting that structural changes related to IBS occur early in brain development. Girls with IBS also showed altered relationships between pain sensitivity and brain structure.